Infrastructure and Economic Performance in sub-Saharan Africa - Arodoye, Nosakhare; Izevbigie John Norense; Richard Usengbuwa (Acta Universitatis Danubius. Œconomica, 2022)
This study examined the impact of infrastructure on economic performance in SSA. By way of a departure from previous study, infrastructure was examined in aggregate and disaggregated terms (transport infrastructure, information communication technology infrastructure and water and sanitation infrastructure) for 39 sub-Saharan African (SSA) countries. Also, to determine the influence/role of institutional quality (governance index) on the impact infrastructure has on economic performance, governance index was interacted with infrastructure index. The result from the s-Generalized Method of Moments (GMM) estimation technique showed that infrastructure index (excluding electricity infrastructure), exerted a direct positive impact on economic performance. The negative impact of electricity infrastructure was rationalized on the basis of poor state of electricity infrastructure in most SSA countries. The estimate from the interactive terms, showed that variables (with the exclusion of information communication technology infrastructure) positively and significantly impacted on economic performance. This shows that governance index influences infrastructure and by extension economic performance in SSA. In addition to Hansen J-statistics test of over-identifying restriction for each of the estimates which affirmed the acceptance of null hypothesis of validity of instruments employed, the none existence of first order (AR (1)) and second order (AR (2)) serial correlation was established. In the light of the findings it was recommended on the average, that governments of the SSA should focus on building strong, virile and resilient infrastructure, and more attention should be directed towards reducing the deficits witnessed in the electricity infrastructure in order to drive greater economic performance.